Multi-dimensional eco-land classification and management for implementing the ecological redline policy in China. (May 2018) - Guo, Xudong; Chang, Qing; Liu, Xiao; Bao, Huimin; Zhang, Yuepeng; Tu, Xueying; Zhu, Chunxia; Lv, Chunyan; Zhang, Yanyu
Abstract: The ecological civilization characterized by the ecological redline policy (ERP) has been a new long-term national development strategy in China. The ERP emphasizes the need to define ecological baseline areas to provide ecosystem services and guarantee the national ecological safety. Eco-land units delineated by the individual spatial boundaries of ecosystems may facilitate an understanding of ecosystem patterns and the associated ecological processes at the landscape level. An eco-land classification system may help to identify and manage ecological baseline areas. In this study, a multi-dimensional eco-land classification system was designed to show how eco-land types could provide a reliable work platform for implementing the ERP and land management. Based on previous studies of eco-land types, we extracted three characteristics comprising the scale dependence, functional dominance, and adaptability of management. These three features were then integrated with the existing land use classification to develop a hierarchical eco-land classification system with four primary classes (fundamental eco-land, auxiliary eco-land, productive eco-land, and daily-life eco-land), 11 secondary classes, and 21 sub-secondary classes. Using a performance index based on spatial overlay analysis, we found that the fundamental eco-land covered up to 65% of the ecological redlining areas at the national scale, but not in some physical geographical regions. Thus, productive eco-land, auxiliary eco-land, and daily-life eco-land were also classified to fill the national level gaps among fundamental eco-lands, where the percentage cover of eco-land types at both the regional and urban scales could exceed 65% of the ecological redlining areas at the corresponding scale. Therefore, the disconnected fundamental eco-lands within ecological redlining areas at the national scale might be linked together as a conterminous green infrastructure if productive, auxiliary, and daily-life eco-land types located in strategic gap sites can be identified and protected at regional and urban scales. The eco-land classification system developed in this study may provide a useful land management framework for implementing the new ERP in China.